E-Faraid system using dynamic rule-based technique / Muhammad Faiz Zafarudin - Zafarudin, Muhammad Faiz (2019)
Faraid is based on the Al-Quran and Al-Sunnah, the consensus of the Prophet’s (Peace and Blessings Be upon Him) companions and their ijtihad the process of making a legal decision by independent interpretation of the legal sources, which is the Al-Quran and Al-Sunnah. In Malaysia, the immovable inheritance assets which have not been claimed by Muslims have been increased yearly. Due to the late application to distribute the assets will cause the process of distribution becomes harder and complicated especially when it involves a few generations of inheritors’ death. Recently, there are many application that are developed to solve the problems that encountered with the rapid development of information technology. There are other application that have been developed to solve Faraid problem, but it does not meet the requirements of users. Thus, this web-based e-Faraid system is developed with the purpose to give guidelines and information to users about distribution property in Islam.